Samarium-Promoted Homocoupling of Benzaldehydes and In Situ Condensation with Esters Under the Catalysis of Cuprous Iodide - Chen, Hongping; Song, Bin; Mi, Mingzhong; Qi, Yan; Liu, Yongjun (Synthesis, 2022)
A novel C–H functionalization method was successfully explored by a reductive three molecule coupling of benzaldehydes and esters mediated by samarium and cuprous iodide; thus, the diarylmethanol skeletons were afforded readily via an in situ esterification in one-pot. Substrates including a variety of esters and different benzaldehydes were investigated, and the desired products were readily obtained in moderate to good yields under mild conditions.
Keywords: samarium; cuprous iodide; benzaldehyde; reductive coupling; diarylmethanol